PERKEMBANGAN OLAHRAGA TRADISIONAL EGRANG PADA REMAJA DI DESA RIDOGALIH KECAMATAN CIBARUSAH - Clinton Tampubolon, Joseven; Ekowati, Ekowati; Nadhirah Qintharah, Yuha (An-Nizam, 2024)
Physical education, namely education through physical activity to achieve physical education goals that have been formulated in the physical, psychomotor, affective and cognitive domains. Physical education contains many elements of sports or games, this activity of playing together is characterized by interaction with other people. Traditional sports are game activities that grow and develop in certain areas, which are full of cultural values and community life values and are taught from generation to generation and traditional sports are the result of the work, tastes and creations of the community which is called culture. For example, in traditional sports, the form of the game is a contest of concentration, balance, dexterity, endurance to cover a certain distance in each column of a predetermined row, where every time the player takes a step they have to maintain their balance to walk forward without falling. return to the starting position to get points. So those who must be involved in socializing the traditional Hadangan sport are the children who aim to preserve the Engrang traditional sports culture so that it does not fade.